Having a Say Matters: Influence of Decision-Making Power on Contraceptive Use among Nigerian Women Ages 35–49 Years - OlaOlorun, Funmilola M.; Hindin, Michelle J. (PLOS ONE, 2014)
Background Research suggests that women of reproductive age who are involved in household decision-making are more likely than those who are not involved to be able to control their fertility. Little is known, however, about this relationship among women at the upper end of the reproductive spectrum. The aim of this study was to determine the association between household decision-making power and modern contraceptive use among Nigerian women ages 35–49 years. Methods A descriptive, cross-sectional study involving a secondary analysis of data from the Nigerian 2008 Demographic and Health Survey was conducted among women ages 35–49 years who were considered to be in need of contraception. The outcome was modern contraceptive use while the main independent variable was a woman's household decision-making power score, constructed using principal component analysis. Multivariate logistic regression was performed to determine whether the women's household decision-making power score, categorized into tertiles, was independently associated with modern contraceptive use. Data were weighted and adjusted for the complex survey design. Results Prevalence of modern contraceptive use among Nigerian women deemed to be in need of contraception in this study was 18.7%. Multivariate logistic regression showed that women's decision-making power remained statistically significantly associated with modern contraceptive use, even after adjusting for age, education, religion, polygyny, parity, wealth and domicile. Women who were in the highest decision-making power tertile had more than one and a half times the odds of using modern contraception compared with women in the lowest tertile [Adjusted Odds Ratio = 1.70; 95% Confidence Interval = 1.31–2.21, p<0.001]. Significance Older Nigerian women who are involved in making household decisions are also able to make decisions related to their fertility. Programs in Nigeria focused on increasing modern contraceptive use should include strategies to increase women's status through encouraging more visible involvement in decision-making across different spheres of their lives.